2015
DOI: 10.1111/pops.12252
|View full text |Cite
|
Sign up to set email alerts
|

Reaching Across the DMZ: Identity Uncertainty and Reunification on the Korean Peninsula

Abstract: Drawing on uncertainty‐identity theory (Hogg, 2012), we explore the effects of uncertainty concerning a specific social identity on group identification and attitudes toward subgroup integration and separation in South Koreans' nested identity context (N = 148). All variables were measured. Path analysis revealed, as predicted, that superordinate identity uncertainty weakened superordinate identification and subgroup identity uncertainty weakened subgroup identification. We also found that subgroup identity un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 23 publications
3
23
0
Order By: Relevance
“…When people are uncertain about themselves, they identify with groups, especially highly entitative groups (Grant & Hogg, 2012;Sherman, Hogg, & Maitner, 2009) and disidentify from low entitative groups or uncertainty-inducing groups (Hogg, Adelman, & Blagg, 2010;Hogg, Meehan, & Farquharson, 2010;Hogg et al, 2007). Directly relevant to the present research, two correlational studies (Jung et al, 2016(Jung et al, , 2018 found a puzzling asymmetry in the relationship between identity-uncertainty and recategorization in the context of hierarchial identities. When people are uncertain about a subgroup which is central to their self-concept, they recategorize and identify more strongly with a superordinate group; however, uncertainty about a superordinate group was not associated with subgroup identification.…”
Section: Self-categorization Depersonalization and Uncertainty Rementioning
confidence: 57%
See 1 more Smart Citation
“…When people are uncertain about themselves, they identify with groups, especially highly entitative groups (Grant & Hogg, 2012;Sherman, Hogg, & Maitner, 2009) and disidentify from low entitative groups or uncertainty-inducing groups (Hogg, Adelman, & Blagg, 2010;Hogg, Meehan, & Farquharson, 2010;Hogg et al, 2007). Directly relevant to the present research, two correlational studies (Jung et al, 2016(Jung et al, , 2018 found a puzzling asymmetry in the relationship between identity-uncertainty and recategorization in the context of hierarchial identities. When people are uncertain about a subgroup which is central to their self-concept, they recategorize and identify more strongly with a superordinate group; however, uncertainty about a superordinate group was not associated with subgroup identification.…”
Section: Self-categorization Depersonalization and Uncertainty Rementioning
confidence: 57%
“…For example, when people feel uncertain about their superordinate identity, subgroups regardless of their status or numerical size may engage in ingroup projection because ownsubgroup attributes are more available and accessible than those of other subgroups. A correlational study by Jung et al (2016) suggests that this is indeed the case. They found that the more superordinate and subgroup attributes overlap, the more strongly subgroup identity uncertainty impedes superordinate identification.…”
Section: Limitations and Future Directionsmentioning
confidence: 93%
“…One response to subgroup identity‐uncertainty is to identify more strongly at the superordinate level, or vice versa. Research confirms this hydraulic mechanism by showing people compensate their subgroup identity‐uncertainty by strengthening their superordinate group identification (Jung, Hogg, & Choi, ).…”
Section: Identity‐uncertainty and The Pursuit Of Subgroup Autonomymentioning
confidence: 82%
“…However, little is known about the effect of identity threat on identity–uncertainty. Identity–uncertainty is a feeling of uncertainty about the social identity defining attributes of a group, and thus about oneself as a group member (Jung, Hogg, & Choi, , ; Jung, Hogg, & Lewis, ; Wagoner, Belavadi, & Jung, )—it readily generates and is caused self‐uncertainty (Hogg, ; Hogg & Mahajan, ). The present study investigates the conditions under which contested views of national history and identity elicit feelings of uncertainty about one's national identity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that decreased perceptions of entitativity can increase group members’ intention to leave their ingroup (Sani, ). Identity–uncertainty has also been found to lead to disidentification from the group (Jung, Hogg, & Choi, , ; Jung, Hogg, & Lewis, ). However, the causal path from reduced entitativity through identity–uncertainty to emigration intention has not been directly tested.…”
Section: Introductionmentioning
confidence: 99%